Incisional surface quality of electron-beam irradiated cornea-extracted lenticule for stromal keratophakia: high nJ-energy vs. low nJ-energy femtosecond laser - Chan, Jian S.; Han, Evelina; Lim, Chris H. L.; Kurz, Arthur C.; Shuman, Jeremy; Liu, Yu-Chi; Riau, Andri K.; Mehta, Jodhbir S. (Frontiers in Medicine, 2023)
Introduction Corneal lenticules can be utilized as an additive material for stromal keratophakia. However, following extraction, they must be reimplanted almost immediately or cryopreserved in lenticule banks. Electron-beam (E-beam) irradiated corneas permit room-temperature storage for up to 2 years, enabling keratophakia to be performed on demand. This study aims to compare the performance of high nano Joule (nJ)-energy (VisuMax) and low nJ-energy (FEMTO LDV) femtosecond laser systems on the thickness consistency and surface quality and collagen morphology of lenticules produced from fresh and E-beamed corneas. Methods A total of 24 lenticules with −6.00 dioptre power were cut in fresh human donor corneas and E-beamed corneas with VisuMax and FEMTO LDV. Before extraction, the thickness of the lenticules was measured with anterior segment-optical coherence tomography (AS-OCT). The incisional surface roughness of extracted lenticules was analyzed using atomic force microscopy (AFM) and scanning electron microscopy (SEM). Multiphoton microscopy was then used to assess the surface collagen morphometry. Results The E-beamed lenticules that were cut using FEMTO LDV were significantly thicker than the fresh specimens as opposed to those created with VisuMax, which had a similar thickness as the fresh lenticules. On the vertex, they were ∼11% thicker than the fresh lenticules. The surface roughness (Rq) of E-beamed lenticules incised with FEMTO LDV did not differ significantly from the fresh lenticules. This contrasted with the VisuMax-fashioned lenticules, which showed notably smoother surfaces (∼36 and ∼20% lower Rq on anterior and posterior surfaces, respectively) on the E-beamed than the fresh lenticules. The FEMTO LDV induced less cumulative changes to the collagen morphology on the surfaces of both fresh and E-beamed lenticules than the VisuMax. Conclusion It has been previously demonstrated that the low nJ-energy FEMTO LDV produced a smoother cutting surface compared to high nJ-energy VisuMax in fresh lenticules. Here, we showed that this effect was also seen in the E-beamed lenticules. In addition, lower laser energy conferred fewer changes to the lenticular surface collagen morphology. The smaller disparity in surface cutting quality and collagen disturbances on the E-beamed lenticules could be beneficial for the early visual recovery of patients who undergo stromal keratophakia.